Experimental generation of fulgurite under realistic lightning discharge conditions - A. Zeynep Çalışkanoğlu; Alessandra S. B. Camara; Corrado Cimarelli; Donald B. Dingwell; Kai-Uwe Hess (Scientific Reports, 2023)
Abstract Fulgurites have been documented in geological deposits from throughout Earth's history. They have also been assigned a potential role in prebiotic chemistry as a source of reactants. Fulgurites are generated in nature by cloud-to-ground lightning strikes. The unpredictability in space and time of the occurrence of lightning events has limited the investigation of both the mechanisms by, and the conditions under, which fulgurites form. A laboratory-based approach can mitigate these limitations. Here, we describe experimentally generated fulgurites generated from Laacher See volcanic ash. We employ a DC source with a trigger-pulse setup in a high voltage laboratory, whose capabilities enable experimental conditions that correspond closely to the electrical characteristics of natural lightning strikes. The experimentally generated fulgurites closely resemble naturally-occurring fulgurites in both state and texture. These experimental investigations yield a high reproducibility of the characteristic of fulgurites generated under well-constrained conditions, enabling some inferences to be made regarding the processes involved in the generation of fulgurites in nature. This work provides a basis for a systematic characterization of experimental fulgurites and the characteristic of lightning discharges.